A review on microstructural characterization of cement-based materials by AC impedance spectroscopy. (July 2019) - Hu, Xiang; Shi, Caijun; Liu, Xiaojin; Zhang, Jiake; de Schutter, Geert
Abstract: As a non-destructive method, AC impedance spectroscopy is a promising technique for the characterization of cement-based materials owing to its advantages in real time monitoring. In this paper, the equivalent circuit models in publications applied for different cement-based systems are summarized. The determinations of hydration properties, microstructural changes and chloride induced corrosion parameters of cement-based materials by AC impedance spectroscopy measurements are reviewed. With some appropriate models, the AC impedance parameters can be applied to characterize microstructure and interfacial properties of cement-based materials. The experimental condition control and data analyses are discussed. Some improvements for measurement device and development of equivalent circuit models for different kinds of binding materials are needed.